Personal finance after 50 - Tyson, Eric (Eric Kevin); Carlson, Robert C., 1957- (--For dummies., 2026)
"Getting to your 50th birthday brings the wisdom that comes with navigating life's ups and downs. It can also bring anxiety if you've not thought ahead to how to manage your finances in your golden years. Don't worry--this book helps you relieve that anxiety. Dig in to discover how to create a solid retirement plan, manage insurance and healthcare costs, get answers to all your estate planning questions, and beyond. Set yourself up with a sustainable financial future, so you can relax and enjoy your second act!"--Provided by publisher.